Dynamic changes occur in the DNA gut virome of female cynomolgus macaques during aging. Issue 2 (1st May 2021) - Tan, Xunmin; Chai, Tingjia; Duan, Jiajia; Wu, Jing; Zhang, Hanping; Li, Yifan; Huang, Yu; Hu, Xi; Zheng, Peng; Song, Jinlin; Ji, Ping; Jin, Xin; et al.
Abstract: Aging is a critical factor affecting physical health and disease in mammals. Emerging evidence indicates that aging may affect the gut bacteriome in cynomolgus macaques, but little is known about whether or how the gut virome changes with age. Here, we compared the DNA gut viral composition of 16 female cynomolgus monkeys ( Macaca fascicularis ) at three life stages (young, adult, and old) using the shotgun metagenome sequencing method. We found that the DNA gut virome from these monkeys differed substantially among the three groups. The gut viruses were dominated by bacteriophages, the most abundant of which was the Caudovirales order (i.e., Siphoviridae, Myoviridae, and Podoviridae families). Additionally, the co‐occurrence analysis revealed that the age‐related bacteriophages were correlated in an extensive and complex manner with the main intestinal bacteria (i.e., Firmicutes, Bacteroidetes, Proteobacteria, and Actinobacteria phyla). Furthermore, the age‐related DNA gut viral functions were enriched for genetic information processing, nucleotide, and folate metabolism. Our gut virome analysis provides new insight into how aging influences the gut virome of non‐human primates. Abstract : We characterized changes of the DNA gut virome associated with age in female crab‐eating macaques. The structural and functional profiles of the gut DNA virome differed significantly among the three age groups. The gut virome was dominated by dsDNA phages, especially the Caudovirales order, which showed strong correlations with the highly prevalent gut bacteria. Our findings suggest that modulating the intestinal virome may be beneficial for the treatment of aging.